Evaluation of Respiratory Symptoms Among Youth e-Cigarette Users - Tackett, Alayna P. (JAMA Netw Open, 2020)
IMPORTANCE: Use of e-cigarettes (ECs) among youths has increased in recent years. e-Cigarette aerosol contains chemical constituents, such as diacetyl or benzaldehyde, which are known to affect the respiratory system. OBJECTIVE: To examine the association between EC use and self-reported wheezing in a cohort of US adolescents. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used data from waves 3 and 4 (October 19, 2015, to January 3, 2018) of the Population Assessment of Tobacco and Health (PATH) study, a longitudinal, nationally representative cohort survey. Adolescent respondents aged 12 to 17 years who did not have asthma were included. EXPOSURES: e-Cigarette use during the previous year. MAIN OUTCOMES AND MEASURES: Self-reported wheezing in the past 12 months (yes or no) and EC use (no use in past year or never use, use in past year, use in past 30 days, and use in past 7 days). Survey-weighted logistic regression models adjusted for demographic characteristics and other risk factors. RESULTS: Among 7049 adolescents without asthma from waves 3 and 4 of the PATH study, 49.9% were female and 54.4% were non-Hispanic White. In unadjusted models, the odds of wheezing in the past 12 months were higher for youths who had used ECs in the past year compared with those who had not (odds ratio, 1.74; 95% CI, 1.22-2.48; P = .003). In the adjusted model, after controlling for the variables of race/ethnicity, household rules about the use of tobacco, contact with a smoker in the previous 7 days, and current use of combustible tobacco products, the association of EC use with wheezing was not significant (adjusted odds ratio for EC use in the past year, 1.37 [95% CI, 0.91-2.05]; in the past 30 days, 1.35 [95% CI, 0.63-2.88]; in the past 7 days, 0.74 [95% CI, 0.28-1.97]; P = .33). CONCLUSIONS AND RELEVANCE: In this cohort study, use of ECs alone was not associated with increased odds of experiencing wheezing episodes. Future studies incorporating the use of objective data appear to be needed to more accurately understand the potential respiratory harms associated with vaping among adolescents.